2018
DOI: 10.1002/ece3.3992
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of parasitic angiosperms in China

Abstract: Parasitic plants are an important component of vegetation worldwide, but their diversity and distribution in China have not been systematically reported. This study aimed to (1) explore floral characteristics of China's parasitic plants, (2) map spatial distribution of diversity of these species, and (3) explore factors influencing the distribution pattern. We compiled a nationwide species list of parasitic plants in China, and for each species, we recorded its phylogeny, endemism, and life form (e.g., herb vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…climate, soil, topography) and biological factors (i.e. hosts, competition, mimicry, herbivory) influence the proper development and survival of parasitic plant populations 18 , 74 , 75 . Also, different parasite-host pairs vary in the overlap of ecological tolerances influencing their habitat distribution 29 .…”
Section: Discussionmentioning
confidence: 99%
“…climate, soil, topography) and biological factors (i.e. hosts, competition, mimicry, herbivory) influence the proper development and survival of parasitic plant populations 18 , 74 , 75 . Also, different parasite-host pairs vary in the overlap of ecological tolerances influencing their habitat distribution 29 .…”
Section: Discussionmentioning
confidence: 99%
“…There were 34 parasitic species belonging to eight families recorded in the flora of Saudi Arabia [39]. However, the number of parasitic plants in Saudi Arabia is much lower than that of Nepal (151) [40], Turkey (146), and China (678 species) [41]. This variation could be attributed to host availability and abiotic stress, which are the key factors affecting the distribution and abundance of parasitic plants or other ecological factors.…”
Section: Discussionmentioning
confidence: 99%
“…In southwest China, Luo et al [60] found only three hosts out of 88 species in the tropical forest that were parasitized by Dendrophthoe pentandra, which indicates that the abundance and host richness of species did not explain the frequency of infections at the sampling unit. Zhang et al [41] reported that the abundance of parasitic plants in a particular site is usually determined by environmental (altitude, area, longitude, and latitude) and biological (dispersal vector and host availability) factors. Host plants' diversity and different kinds of habitats can also influence the spreading and density of parasitic species [61].…”
Section: Discussionmentioning
confidence: 99%
“…The growth and distribution of parasitic plants are influenced by environmental factors (i.e., climate, soil, topography), and by biological factors (i.e., competition, mimicry, herbivory) ( Heide-Jørgensen, 2008 ; Zhang et al, 2018 ; Jiang and Zhang, 2021 ). Based on ArcGIS-based MaxEnt modeling, we found that among the four parasite-host pairs, Cynomorium songaricum and Nitraria sibirica had two common climate factors: Bio7 and Bio17, Boschniakia rossica and Alnus mandshurica also had two ones: Bio4 and Bio14 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%